2016
DOI: 10.1111/josh.12428
|View full text |Cite
|
Sign up to set email alerts
|

A School‐Based Program for Overweight and Obese Adolescents: A Randomized Controlled Trial

Abstract: BACKGROUND Given the dramatic increase in adolescent overweight and obesity, models are needed for implementing weight management treatment through readily accessible venues. We evaluated the acceptability and efficacy of a school-based intervention consisting of school nurse-delivered counseling and an afterschool exercise program in improving diet, activity, and body mass index (BMI) among overweight and obese adolescents. METHODS A pair-matched cluster-randomized controlled school-based trial was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
123
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(127 citation statements)
references
References 25 publications
1
123
0
3
Order By: Relevance
“…Such factors only intensify physiological, hormonal, and metabolic resistance to weight loss (Farias, Cuevas, & Rodriguez, 2011; Müller, Bosy-Westphal, & Heymsfield, 2010). Therefore, school-based obesity interventions can only be expected to have modest effects (Elbel, Corcoran, & Schwartz, 2016); meaningful reduction in obesity rates will require multifaceted societal change (Block & Roberto, 2014; Pbert et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such factors only intensify physiological, hormonal, and metabolic resistance to weight loss (Farias, Cuevas, & Rodriguez, 2011; Müller, Bosy-Westphal, & Heymsfield, 2010). Therefore, school-based obesity interventions can only be expected to have modest effects (Elbel, Corcoran, & Schwartz, 2016); meaningful reduction in obesity rates will require multifaceted societal change (Block & Roberto, 2014; Pbert et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…However, school nurses have been only involved in a limited amount of school-based obesity interventions (Pbert et al, 2016; Schroeder, Travers, & Smaldone, 2016). No school nurse-led intervention for children with severe obesity has been previously implemented or evaluated (Schroeder et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, school‐based programs—designed to be completed with peers who positively and consistently support and encourage each other—should be developed to increase PA levels and decrease obesity rates among adolescents . Furthermore, a scenario where school nurses, in addition to providing individual health counseling and after‐school exercise programs at school, also facilitate peer group activity programs in the community, might be worth consideration …”
Section: Implications For School Healthmentioning
confidence: 99%
“…In addition, social support from classmates, as an interpersonal factor, is an important contributor to the psychosocial functioning of obese youth and to the peer health spillover effect, in a school context . Recently, it was observed that intervention programs at the individual level were not effective, without changes being made to the environment . In addition, social and environmental factors that lead to high‐fat, high‐calorie eating habits and decreased physical activities have been suggested as the main factors contributing to the increase of obesity rates .…”
mentioning
confidence: 99%
See 1 more Smart Citation